1980
DOI: 10.1071/ch9802737
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Australian soft corals. XXII. The structures of two novel sesquiterpenes and a nor sesquiterpene from Lemnalia africana, confirmed by a single-crystal X-ray study

Abstract: The isolation of two new sesquiterpenes (3) and (8) and a novel nor sesquiterpene (16) from Lemnalia africana is reported. In each case, the absolute stereochemistry was deduced chemically and spectroscopically, and confirmed by a single-crystal X-ray study on a suitable derivative (7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…17) The relative stereochemistry of 3 was deduced from a 2D NOESY experiment, which showed similar results as described for 1. The structure of elongatol C (3) was thus determined as lemnal-1(10)-en-2b,12a-diol.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…17) The relative stereochemistry of 3 was deduced from a 2D NOESY experiment, which showed similar results as described for 1. The structure of elongatol C (3) was thus determined as lemnal-1(10)-en-2b,12a-diol.…”
mentioning
confidence: 66%
“…17) The relative stereochemistry of 6 was deduced from a 2D NOESY experiment, which indicated that Me-13, Me-14, Me-15, H-6, and H-12 are on one side of the molecule, while H-4, H-7, and H-11 are on the opposite side of the molecule (Fig. 4).…”
mentioning
confidence: 99%
“…The R-configuration of the C-2 hydroxy group was determined by comparing the J 1,2 value of 3 with those of elongatol A (f), isolated from Nephthea elongata 10 ( Figure 2) and its 2-epimer analogue (0 Hz). 6,18 The second isolated compound from R. fulVum fulVum, nardosinanol D (4), was assigned with the elemental formula C 16 H 26 O 4 , as shown by its CIMS and 13 C NMR spectra. That the m/z 265 peak agrees with [M + H -H 2 O] + was clear from the required four oxygen atoms ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The absolute stereochemistries of several nardosinanoids isolated from the soft corals of the genera Paralemnalia and Lemnalia also had been determined. 1,4,[7][8][9][10][11][12][13] On the basis of the above results and biogenic consideration, the absolute configurations at C-1 and C-12 of neolemnanoids were considered to be identical as illustrated in formula 1-6. Thus, the absolute structures of 1-6 were established.…”
Section: Neolemnane-type Sesquiterpenoids From a Formosan Soft Coral mentioning
confidence: 99%
“…
Soft corals belonging to the genera Paralemnalia [1][2][3][4] and Lemnalia [5][6][7][8][9][10][11][12] have been found to be a rich source of neolemnane and nardosinane sesquiterpenoids. Our previous investigation on the chemical constituents of a soft coral Paralemnalia thyrsoides has resulted in the isolation of three terpenoids, paralemnolins A-C.

13) Continuing study on searching new metabolites of this soft coral again afforded six new metabolites paralemnolins D-I (1-6) (neolemnanoids).

…”
mentioning
confidence: 99%